reConsidering Culture in Research: Attracting and Retaining Culturally Diverse Research Participants - Cheri L. Hatcher (Adult Education Research Conference, 2022)
The U.S. Census projects that by 2060, minorities will comprise 60 percent of the population, presenting challenges to researchers using human subjects with widening cultural, gender, identity, and disability characteristics.
Keywords: diversity in research; globalized research; inclusive research; intersectionality in research participants; research participant diversity